OTENTISITAS HADIS DALAM DISKURSUS SARJANA KONTEMPORER: ANALISIS PEMIKIRAN AHMAD AMIN DAN MUSTAFA SIBA’I - Nur Kholis (Al Naqdu, 2025)
This research aims to reveal fundamental issues regarding views on the authenticity of hadith, based on the historical context of hadith, particularly in relation to the Prophet’s statement about lying upon him. This discussion is essential for capturing the contemporary scholarly debate surrounding hadith authenticity, where arguments often rely on analysis of the hadith concerning falsehoods attributed to the Prophet. This debate serves as a crucial focal point in arguments about hadith authenticity, which has significant implications for the discourse on the reliability of hadith as a valid source of guidance in Islam. This research employs a qualitative approach through a literature study. The study focuses on the thoughts of Ahmad Amin and Mustafa Sibai, highlighting their critical arguments on the issue. The research finds that Ahmad Amin suggests, albeit tentatively, the possibility of hadith fabrication during the Prophet's time, based on the hadith man kazzaba alayya (“whoever lies about me”). The credibility of the Prophet’s Companions is also a central theme, linking to the potential for hadith fabrication in the Prophet’s era. Additionally, post-Prophetic hadith fabrication is another important topic discussed, demonstrating Ahmad Amin's consistent stance on the critique of hadith authenticity. Keywords: Hadith Authenticity, Modern Scholars, Ahmad Amin, Sibai